The olive branch from Palestine : the Palestinian declaration of independence and the path out of the current impasse - Segal, Jerome M., 1943- (University of California Press, 2022)
"In The Olive Branch from Palestine, Segal provides in the first part an analytical and historical study of the 1988 Declaration, a remarkable act of unilateral peacemaking through which the PLO accepted the legitimacy of the 1947 Partition Resolution and thereby redefined Palestinian nationalism. In the second part, he proposes a new strategy based on solutions to the two core issues of 1948: the preservation of a Jewish state, and the rights and circumstances of Palestinian refugees. With The Olive Branch from Palestine, Jerome Segal offers a new narrative of the peace process and details a Palestinian-led strategy that could end the conflict"--